Young brown dwarfs and their environments : testing star and planet formation - Dawson, Paul (Trinity College (Dublin, Ireland). School of Physics, 2014)
This thesis presents a new contribution to our understanding of the formation of brown dwarfs. From a description of their discovery, to an analysis of their disks and photospheres, it sheds new light on the conditions under which stars, brown dwarfs, and planets, form and evolve. It explores new challenges to further studies of young brown dwarfs, and offers a means of advance.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin